Predicting the progression of chronic subdural hematoma based on skull density - Yang, Weijian; Chen, Qifang; Yao, Haijun; Zhang, Jun; Zhang, Quan; Fang, Jiang; Wu, Gang; Hu, Jin (Frontiers in Neurology, 2023)
Objective The objective of this study was to investigate potential correlations between skull density and the progression of chronic subdural hematoma (CSDH). Methods Patients with unilateral CSDH were retrospectively enrolled between January 2018 and December 2022. Demographic and clinical characteristics, as well as hematoma and skull density (Hounsfield unit, Hu), were collected and analyzed. Results The study enrolled 830 patients with unilateral CSDH until the resolution of the CDSH or progressed with surgical treatment. Of the total, 488 patients (58.80%) necessitated surgical treatment. The study identified a significant correlation between the progression of CSDH and three variables: minimum skull density (MiSD), maximum skull density (MaSD), and skull density difference (SDD) (p < 0.001). Additionally, in the multivariable regression analysis, MiSD, MaSD, and SDD were independent predictors of CSDH progression. The MiSD + SDD model exhibited an accuracy of 0.88, as determined by the area under the receiver operating characteristic curve, with a sensitivity of 0.77 and specificity of 0.88. The model’s accuracy was validated through additional analysis. Conclusion The findings suggest a significant correlation between skull density and the CSDH progression.